Formulasi Krim Ekstrak Etanol Herba Patah Tulang (Euphorbia tirucalli L) 10% Dengan Variasi Nilai Hlb Tween 80 Dan Span 80 Sebagai Emulsifying Agent - julia megawati; Nurul Farida; Wahid Sabaan; Yulis Trinovitasari (Universitas Muhammadiyah Klaten, 2020)
Euphorbia tirucalli L is a plant that has antimicrobial, antioxidant, antiviral, immunomodulatory properties, numb feet and hands. Euphorbia tirucalli L contain compounds including flavonoids and tannins. The research objective was to determine the differences in cream formulations with variations in the HLB values ​​of tween 80 and span 80 as emulsifying agents, to test the physical properties and stability of the cream preparations. Fractures were macerated extracted using ethanol 96% solvent. The resulting viscous extract was formulated in the form of cream type A / M with variations of Tween 80 and Span 80, the stability of the cream preparations obtained were tested for their stability including organoleptic, homogeneity, pH, adhesion, dispersion and viscosity testing, then continued by using the freeze thaw testing method. The results showed that the fracture herb ethanol extract could be formulated into a cream preparation that met the criteria by using tween 80 1.26 grams and span 80 3.74 grams with an HLB value of 7.